Monstrous to our human reason. The empty grave of the Winter’s tale - Richard Wilson (Sillages Critiques)
The Winter’s Tale is haunted by the fear that its ending is as ‘monstrous to our human reason’ as it would be for a deceased man ‘to break his grave / And come again’. Thus Leontes imagines a dead Hermione might ‘possess her corpse, and on this stage… appear soul-vexed’, and Paulina warns that ‘the ghost that walked’ would ‘shriek that even your ears / Should rift to hear’ it cry ‘Remember’. Earlier Antigonus indeed described the ‘queen’s ghost’ with eyes like ‘two spouts’, as ‘with shrieks / She melted into air’. So when ‘the Queen’s picture’ moves, and ‘it appears she lives’, the play represses possibilities that are ‘more monstrous standing by’, and which had been Shakespeare’s concern ever since Juliet shuddered at ‘the horrible conceit’ of premature burial. The statue that comes to life reverses the contretemps of Juliet’s game of playing saints that ‘do not move’. But The Winter’s Tale can never separate the ‘joy and terror’ in its own anachronistic ‘o’erthrow’ of temporal order, nor suppress the horror of bones that ‘Have burst their cerements’ in the uncanny story of the man ‘Dwelt by a churchyard’.